Investigando o papel da masturbação na sexualidade da mulher - Baumel, Sérgio Werner (2014)
This work has intended to investigate contemporary Brazilian female sexuality. Its main hypothesis was that masturbation is important for healthy female sexual function and female sexual satisfaction, and that guilt, values and negative attitudes are implicated in that correlation. Two separate trials have been conducted. In the first trial, evocations were used with the induction terms Woman who masturbates and Man who masturbates, to investigate Social Representations of masturbation for 113 male students and 135 female students from Espírito Santo Federal University, with ages varying from 18 to 30 years old. The results point to a transition process in the Social Representations, with the persistence of elements related to traditional attitudes and gender double standard but, at the same time, already showing elements related to pleasure, freedom and self-knowledge in the central cores of the Social Representations. In the second trial were investigated practices and attitudes towards masturbation, sexual function, sexual satisfaction, sex guilt and personal values of 1796 Brazilian women aged 18 to 66 years (M = 29,4; DP = 9,58), from every region in the country, who voluntarily and anonymously answered to an online survey, which included: sociodemographic data, the Female Sexual Function Index, Mosher Abreviated Sex Guilt Scale, questions directly related to practices and attitudes towards masturbation, the reduced version of the Marlowe-Crowne Social Desirability Scale, the Sexual Satisfaction Scale for Women and the Basic Values Questionnaire. Results showed that masturbation positively influences female sexual function, but not sexual satisfaction. Sex guilt negatively influences sexual satisfaction, sexual function and masturbation habit. These variables are also negatively influenced by materialistic human values and positively influenced by humanistic human values. Despite several limitations of this study, it is suggested that actions to improve information, about sexuality as a whole and about masturbation in particular, in the areas of education and health, may contribute to decrease sexual guilt and the damages it may cause to Brazilian women’s sexual health.